Highly cooperative fluorescence switching of self-assembled squaraine dye at tunable threshold temperatures using thermosensitive nanovesicles for optical sensing and imaging - Sou, Keitaro (2020)
Thermosensitive fluorescent dyes can convert thermal signals into optical signals as a molecular nanoprobe. These nanoprobes are playing an increasingly important part in optical temperature sensing and imaging at the nano- and microscale. However, the ability of a fluorescent dye itself has sensitivity and accuracy limitations. Here we present a molecular strategy based on self-assembly to overcome such limitations. We found that thermosensitive nanovesicles composed of lipids and a unique fluorescent dye exhibit fluorescence switching characteristics at a threshold temperature. The switch is rapid and reversible and has a high signal to background ratio (>60), and is also highly sensitive to temperature (10-22%/°C) around the threshold value. Furthermore, the threshold temperature at which fluorescence switching is induced, can be tuned according to the phase transition temperature of the lipid bilayer membrane forming the nanovesicles. Spectroscopic analysis indicated that the fluorescence switching is induced by the aggregation-caused quenching and disaggregation-induced emission of the fluorescent dye in a cooperative response to the thermotropic phase transition of the membrane. This mechanism presents a useful approach for chemical and material design to develop fluorescent nanomaterials with superior fluorescence sensitivity to thermal signals for optical temperature sensing and imaging at the nano- and microscales.